Material Parts in Social Structures - Dave Elder-Vass (Journal of Social Ontology, 2017)
There has been much debate on whether and how groups of human agents can constitute social structures with causal significance. Both sides in this debate, however, implicitly privilege human individuals over non-human material objects and tend to ignore the possibility that such objects might also play a significant role in social structures. This paper argues that social entities are often composed of both human agents and non-human material objects, and that both may make essential contributions to their causal influence. In such cases the causal influence of social structures should be attributed to the emergent causal powers of what I call socio-technical entities.